World Development Report 2006 : Equity and Development - World Bank (Washington, DC, 2012)
This year’s Word Development Report (WDR), the twenty-eighth, looks at the role of equity in the development process. It defines equity in terms of two basic principles. The first is equal opportunities: that a person’s chances in life should be determined by his or her talents and efforts, rather than by pre-determined circumstances such as race, gender, social or family background. The second principle is the avoidance of extreme deprivation in outcomes, particularly in health, education and consumption levels. This principle thus includes the objective of poverty reduction.